2013
DOI: 10.2147/hiv.s50171
|View full text |Cite
|
Sign up to set email alerts
|

HIV prevalence among the female sex workers in major cities in Myanmar and the risk behaviors associated with it

Abstract: BackgroundMyanmar is one of the countries hardest hit by the human immunodeficiency virus (HIV) epidemic in Asia.AimThe objective of the study was to determine HIV prevalence among the female sex workers in major cities in Myanmar and the risk behaviors associated with it.MethodsThis cross-sectional study was conducted among female sex workers in major cities in Myanmar. Interviews were conducted by trained research assistants, in private, using a questionnaire. The HIV status of the respondents was asked and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Overall 8.5 % of new tuberculosis patients are HIV sero-positive in Myanmar, but information about age and sex differences in TB-HIV co-infection is not available [ 39 ]. Studies of female sex workers in Myanmar have indicated higher HIV prevalence in younger women [ 40 ]; HIV-TB co-infection in Myanmar, and its impact on the tuberculosis epidemic, requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Overall 8.5 % of new tuberculosis patients are HIV sero-positive in Myanmar, but information about age and sex differences in TB-HIV co-infection is not available [ 39 ]. Studies of female sex workers in Myanmar have indicated higher HIV prevalence in younger women [ 40 ]; HIV-TB co-infection in Myanmar, and its impact on the tuberculosis epidemic, requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…According to the 2011 HIV sentinel serosurveillance, HIV prevalence rates among FSW dropped from 18.4% in 2008 to 9.4% in 2012. 77 It is estimated that there are 40,000 to 80,000 FSW in Myanmar. The number of MSM is estimated at 240,000, mostly in Yangon and Mandalay, with an overall HIV prevalence of 7.8% (Mandalay 9%, Yangon 5%), with more than 81% having used a condom at last sex.…”
Section: Myanmarmentioning
confidence: 99%
“…[13] Although our sample was older (median 36 vs 30 years) than the IBBS sample and other surveys [13,38,39] and with lower reported illiteracy (4.6% vs 15.7%). [39] National AIDS Programme guidelines recommend HIV testing every 6 months, but the median time between tests was 1.1 years among our sample with 38.3% of clients not being tested at all and only 26.4% with repeat tests.…”
Section: Discussionmentioning
confidence: 99%